EXPRESS: Effect of oral gabapentin administered in-hospital on behavioral stress, compliance, and physiologic stress markers: a randomized, double-blind, placebo-controlled trial - Camille Canosa; Stacie C Summers (Journal of Feline Medicine and Surgery, 2026)
Objectives: The aim of the study was to determine whether post-admission oral gabapentin improves stress indices and handling tolerance in hospitalized cats. Methods: In this double-blind, randomized, placebo-controlled, parallel-design trial, healthy client-owned cats were enrolled. After initial exam, cats received a 100-mg gabapentin or placebo capsule. At ninety minutes, a second examination, venipuncture, and brief dorsal positioning were performed. Five stress behaviors (struggling, vocalization, repelling, hypersalivation, mouth breathing), compliance, and enclosure activity score (1, sedate; 5, very active) were recorded; blood glucose, lactate, serum cortisol, and lymphocyte count were measured. Serum gabapentin concentrations were obtained 90-minutes post-capsule. Results: Thirty cats (15 cats/group) were included in analysis. In the 15 cats that received gabapentin, median gabapentin dose was 21.7 mg/kg (range, 14.3–28.1 mg/kg), yielding a median serum concentration 16.4 mcg/mL (range, 1.3–24.5 mcg/mL). Most cats gabapentin-treated cats exhibited less stress behaviors (86%; 13/15) and better compliance for handling during examination (73%; 11/15) at 90-minutes post-capsule compared with 20% (3/15) and 26% (4/15), respectively, in placebo cats. Between group differences were not detected for behavioral or compliance scores during venipuncture or dorsal positioning. Enclosure activity scores in the gabapentin group decreased from median 3 at baseline to 2 from 90–360 minutes post dose (120, 240, and 300 minutes; P